Rehabilitation of a Bilateral Maxillectomy Patient with a Free Fibula Osteocutaneous Flap and with an Implant‐Retained Obturator: A Clinical Report. Issue 4 (29th July 2015) - Otomaru, Takafumi; Sumita, Yuka I.; Aimaijiang, Yiliyaer; Munakata, Motohiro; Tachikawa, Noriko; Kasugai, Shohei; Taniguchi, Hisashi
Abstract: A 47‐year‐old man underwent surgical resection and reconstruction with a fibula osteocutaneous flap. After the surgery, a surgical obturator was placed and adjusted. After flap healing, a conventional obturator was fabricated with polymethyl methacrylate resin and retained by the anatomical undercuts around the reconstructed fibula bone flap and the posterior part of the defect. As the defect shape changed with time, a second conventional obturator was fabricated and fitted. No further recurrence of myoepithelioma was observed for 2 years, and the patient was satisfied with the obturator during mastication and speech; however, despite having no major complaints, the patient found it difficult to chew on the right side, and the obturator was displaced slightly downward when the mouth was opened wide and shifted when chewing hard and sticky food. Thus, an implant‐retained obturator was suggested to provide better retention and stability. Four dental implants were therefore placed into the fibula bone, although one did not osseointegrate because either primary stability was insufficient or overload was affected in the nonloaded implant environment and was replaced. After fitting custom abutments with a magnet, an implant‐retained obturator was placed, and the patient was satisfied with the outcome. During 3 years of follow‐up, no issues were noted with the implant bodies, abutments, obturator, or reconstructed site. The conventional obturator was displaced slightly downward when the patient opened his mouth wide, and it shifted when chewing hard and sticky food because there was limited fibula bone at the reconstruction site and more available posteriorly. For better retention and stability, the implant‐retained obturator was fabricated with a custom abutment and magnetic retention. The patient was satisfied with the results, as improved implant retention increased the stability of the prosthesis. This clinical report describes the rehabilitation of a bilateral maxillectomy patient with a free fibula osteocutaneous flap and an implant‐retained obturator. The patient's oral functions were improved when the prosthesis was stabilized by means of dental implants and custom abutments.